English language vocabulary acquisition in first grade learners - Heredia Tipán, Carmen Mercedes (2023)
Nowadays, it is evident that English is gradually gaining strength as a global language, that is why the teaching of the language must be taken into account from the formative years. The acquisition of vocabulary in first grade is essential to create a strong foundation in vocabulary knowledge. Nonetheless, in Ecuador there is no Curricular Reform that alludes to English as a mandatory subject. The present study aims to determine the level of English language vocabulary acquisition in first grade children of the 'Once de Noviembre' Educational Institution through tests of vocabulary knowledge after have been exposed to the English language at early ages. The methodology used for this research was qualitative supported by a quantitative data with an explorative, diagnostic and descriptive approach. The population used for this research was 39 boys and girls of 4-5 years of age of the first grade "A" of the ‘Once de Noviembre’ Educational Institution from the Province of Cotopaxi, Latacunga canton, Ignacio Flores neighborhood, La Laguna sector. Different tests (comprehension and production), a checklist and an unstructured interview with the children's teacher tutor were used as data collection instruments. The results showed that after the interaction with the students of the pre-professional teaching practices the learners have a high level of English language vocabulary acquisition, which means that they also have an active vocabulary. In conclusion, the research results provide insightful ideas for improving the English language teaching process in comprehension, and production of the language at an early age